Romance Formula Potrayed in The Gift of The Magi Short Story by O. Henry - Firsta, Fanisa Zahrani; Salsabila, Nadira; Rohmana, Wahyu Indah Mala (English Education and Literature Journal (E-Jou), 2025)
This research aims to find out how romance formulation is applied in shaping the storyline of "The Gift of the Magi". Because in previous studies, no one has studied this short story in terms of its plot. Then the researcher analyzes the elements of the plot in the short story The Gift of the Magi based on Cawelti''s romance formula.This research uses qualitative research methods. This is the qualitative methodology part of the research design. The researchers use theory by Cawelti “Romance formula" to find the data from O. Henry''s short story entitled The Gift of the Magi published in 1905. The storyline of "The Gift of The Magi" can categorized into four stages : (1) the first is about their love story as marriage couple (2) thinking about christmas gift for each other while they don’t have money (3) the obstacle tells that Della excitedly presents Jim with a platinum chain for his pocket watch, hoping to please him, but learns that Jim has sold his watch to buy her the dream comb she adores, revealing their selfless sacrifice for each other (4) In the end, Jim and Della, despite sacrificing their prized possessions, find joy in the tradition of gift-giving, embodying the true spirit of Christmas as modern-day Magi. The researcher hopes this study will offer extensive exploration and new insights into literature